Conhecimento, atitude e prática sobre o processo de doação de órgãos e tecidos entre profissionais de saúde - Lima, Angela Beatriz de Castro (2018)
Introduction: The process of organs and tissues donating requires the involvement of several health professionals. The professionals involved in the Intra-Hospital Organ and Tissue Donation and Transplant Commissions (CIHDOTTs) are dedicated to conducting the donation and orientation process on the maintenance of the potential donor (PD) of organs and tissues, so it is necessary to study how such professionals understand the stages of this process. Objective: To analyze the knowledge, attitude and practice about the process of donation of organs and tissues among professionals working in CIHDOTTs. Methods: This dissertation consists of two interdependent studies: a methodological study for the construction and validation of face and content of a questionnaire about Knowledge, Attitude and Practice; and an analytical study. In the methodological study the population was formed by the judges who participated in the process of validation of the face and content of the questionnaire elaborated. There were 9 judges with at least one year of performance in the Transplant Center of a state in the southeastern region of Brazil.